Strategi Pengembangan Agribisnis Peternakan Ayam Ras Petelur Di Kabupaten Kediri - Agung Dwi Cahyo (Manajemen Agribisnis: Jurnal Agribisnis, 2019)
This research is conducted to determined the suitable strategy towed agribusiness development of layer chicken livestock, by understanding the business owner profile to analyse SWOT (strenght, weakness, opportunity, threat) factor. Agribusiness perform important role, it includes production circle, yield processing, and product selling. Strategy analysis is cundected in external and internal environment. Beside that, the demand of highnutrient chicken egg keep increasing annually. Through this strategy to exploit and to create a new opportunity must be supported by missions, purpose, and the environment codition, and it is expected to mee the demand of chicken population increase among business owner especially in kediri ration. The research was using descriptive method by collecting variabels of the size ofeach individu, interview equipment, and questions list in quisioner,sampling method was random sampling to 15 person business owner in three different villages in regency kediri. The criteria of the interviewee was business owner with around 500 to 10.000 chicken populations. Layer chicken business is a promising business because a chicken can produce averagely 250 to 280 egg per year, the chicken must be maintained based on environment standard including cage sanitation and quality of the food. There are 3 stage of growing layer chicken, thy are starter stage, grower stage and layer stage. The biggest output in chicken livestock is the feed. Therefore, self produced feed is the one becomes the most suggested by mixing the cornmill and consentrate to minimalize the cost. Based on the date from central bureau of statistic, the demand of chicken eggs are still realtively high, because egg has been known as one of food material that contain good nutrition. Thanks to the cooperation relation between business owner, middle man, and village local cooperation which can increase the income of local business owner. Ngancar with it’s strategic location provide practical egg distribution to the middle man or the cansument. Therefore, SWOT, EFAS, IFAS analysis application are suitable to the chicken business development, either for present condition or the future, also considering the price fluctuation can be considered as a threat to the business owner, hopefully this research may give solution to change the threat into the new opportunity to increase the quality of layer chicken livestock around kediri regency